Indirect effects of bottom fishing on the productivity of marine fish. Issue 4 (28th October 2016) - Collie, Jeremy; Hiddink, Jan Geert; van Kooten, Tobias; Rijnsdorp, Adriaan D; Kaiser, Michel J; Jennings, Simon; Hilborn, Ray
Abstract: One quarter of marine fish production is caught with bottom trawls and dredges on continental shelves around the world. Towed bottom‐fishing gears typically kill 20–50 per cent of the benthic invertebrates in their path, depending on gear type, substrate and vulnerability of particular taxa. Particularly vulnerable are epifaunal species, which stabilize the sediment and provide habitat for benthic invertebrates. To identify the habitats, fisheries or target species most likely to be affected, we review evidence of the indirect effects of bottom fishing on fish production. Recent studies have found differences in the diets of certain species in relation to bottom fishing intensity, thereby linking demersal fish to their benthic habitats at spatial scales of 10 km. Bottom fishing affects diet composition and prey quality rather than the amount of prey consumed; scavenging of discarded by‐catch makes only a small contribution to yearly food intake. Flatfish may benefit from light trawling levels on sandy seabeds, while higher‐intensity trawling on more vulnerable habitats has a negative effect. Models suggest that reduction in the carrying capacity of habitats by bottom fishing could lead to lower equilibrium yield and a lower level of fishing mortality to obtain maximum yield. Trawling effort is patchily distributed – small fractions of fishing grounds are heavily fished, while large fractions are lightly fished or unfished. This patchiness, coupled with the foraging behaviour of demersal fish, may mitigate the indirect effects of bottom fishing on fish productivity. Current research attempts to scale up these localized effects to the population level.